2017
DOI: 10.12705/664.1
|View full text |Cite
|
Sign up to set email alerts
|

Troubles with mycorrhizal mushroom identification where morphological differentiation lags behind barcode sequence divergence

Abstract: Species of Russula (Russulaceae), a large, cosmopolitan, ectomycorrhizal fungal genus are notoriously difficult to identify. To delimit species and to evaluate their morphology, we sequenced the ~400 bp ITS2 ribosomal DNA region from 713 Pacific Northwest Russula specimens from Benjamin Woo's exceptional collection. As a topological constraint for analysis of the ITS2, we sequenced and inferred a phylogeny from the ITS, LSU, RPB2 and EF1-α regions from 50 European and North American specimens of major clades i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 109 publications
(142 reference statements)
2
27
0
Order By: Relevance
“…We sequenced the ITS region of 604 mushroom specimens representing 289 species from 75 genera deposited in the Beaty Biodiversity Museum (UBC Herbarium). DNA extraction was as in Bazzicalupo et al (). The Canada Michael Smith Genome Sciences Centre (Vancouver, BC) performed PCR and sequencing using primers ITS1F (Gardes & Bruns, ) and ITS4 (White, Bruns, Lee, & Taylor, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We sequenced the ITS region of 604 mushroom specimens representing 289 species from 75 genera deposited in the Beaty Biodiversity Museum (UBC Herbarium). DNA extraction was as in Bazzicalupo et al (). The Canada Michael Smith Genome Sciences Centre (Vancouver, BC) performed PCR and sequencing using primers ITS1F (Gardes & Bruns, ) and ITS4 (White, Bruns, Lee, & Taylor, ).…”
Section: Methodsmentioning
confidence: 99%
“…Fungi play essential roles in terrestrial ecosystems by decaying wood, causing diseases of plants, or forming mycorrhizal partnerships. With increasing global CO 2 levels and temperatures, fungal geographic ranges may expand (Pringle, Adams, Cross, & Bruns, 2009) or contract (Ellis, Coppins, Dawson, & Seaward, 2007) potentially altering rates of wood decay (Allison & Treseder, 2008) or increasing plants' susceptibility to fungal infections (Chen et al, 2007). Elucidating distributional ranges is important for predicting shifts in key ecosystem services that may accompany environmental change (Peay, Bidartondo, & Arnold, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Current studies suggest that Russula species reported from multiple continents are mainly boreal-arctic taxa. Bazzicalupo et al (2017) found that 17 of 72 Russula species from the Northwest of the USA (mostly from boreal-arctic areas) matched a sequence of European barcoded taxa. Accordingly, Geml et al (2012) suggested that long distance dispersal and gene flow between boreal-arctic species of the Russulaceae (Russula and Lactarius) was common.…”
Section: Introductionmentioning
confidence: 97%
“…-Are dependent on the chosen similarity cut-off for species recognition. The often applied 97% similarity cut-off (Lindahl et al 2013;Selosse et al 2016) is certainly too low for most mushrooms as suggested by several recent taxonomic revisions (Bazzicalupo et al 2017;Yuan 2014;Miettinen et al 2018;Ö rstadius et al 2015). -Can be affected by contamination problems, e.g.…”
Section: Introductionmentioning
confidence: 99%